2016
DOI: 10.4062/biomolther.2015.088
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-Triggered Resolvin D1 Inhibits TGF-β1-Induced EndMT through Increasing the Expression of Smad7 and Is Closely Related to Oxidative Stress

Abstract: The endothelial-mesenchymal transition (EndMT) is known to be involved in the transformation of vascular endothelial cells to mesenchymal cells. EndMT has been confirmed that occur in various pathologic conditions. Transforming growth factor β1 (TGF-β1) is a potent stimulator of the vascular endothelial to mesenchymal transition (EMT). Aspirin-triggered resolvin D1 (ATRvD1) has been known to be involved in the resolution of inflammation, but whether it has effects on TGF-β1-induced EndMT is not yet clear. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…In the present study, we found that the TGF-b/Smad and Akt/mTOR/p70S6K signalling pathways are required for TGF-b1-induced EndMT, whereas p38 MAPK, Erk 1/2 and JNK signals are not essential for this specific transduction process. Our results confirm those of a number of studies which have confirmed that TGF-b1 is associated with the pathogenesis of EndMT [30][31][32]. Both resident kidney cells and infiltrating leukocytes can secrete TGF-b1, and canonical TGF-b signal transduction involves consecutive processes that include binding of TGF-b1 to TGF-b receptor type II (TGF-bRII), which recruits and phosphorylates TGF-b receptor type I (TGF-bRI) and subsequently activates Smad complexes, which consist of phosphorylated Smad 2/3 and the Cosmad (Smad 4).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found that the TGF-b/Smad and Akt/mTOR/p70S6K signalling pathways are required for TGF-b1-induced EndMT, whereas p38 MAPK, Erk 1/2 and JNK signals are not essential for this specific transduction process. Our results confirm those of a number of studies which have confirmed that TGF-b1 is associated with the pathogenesis of EndMT [30][31][32]. Both resident kidney cells and infiltrating leukocytes can secrete TGF-b1, and canonical TGF-b signal transduction involves consecutive processes that include binding of TGF-b1 to TGF-b receptor type II (TGF-bRII), which recruits and phosphorylates TGF-b receptor type I (TGF-bRI) and subsequently activates Smad complexes, which consist of phosphorylated Smad 2/3 and the Cosmad (Smad 4).…”
Section: Discussionsupporting
confidence: 92%
“…Notably, it is specifically TGFb2 which is upregulated among the TGFb-family members on mRNA level, and which is also detected as mature TGFb2 in the secretome of endothelial cells upon hypoxia. While in context of fibrosis, the most abundant isoform within fibrotic tissue which had been identified as EndMT-inducing stimulus was TGFb1 [29]. Our observation here is in line with several previous publications which identified TGFb2 as most potent EndMT-inducing stimulus (without negating EndMT-inducing potential of TGFb1) [30][31][32].…”
Section: Discussionsupporting
confidence: 91%
“…These results suggested that EOFAZ inhibits TGF-β1-induced KLF4 and NF-κB activation. A previous study reported that NF-κB is one of key regulators during EndMT in endothelial cells; activation or inhibition of the NF-κB signaling pathway resulted in EndMT reversal (28). In addition, it has been reported that NF-κB is essential for both the induction and maintenance of EndMT (29).…”
Section: Effect Of Eofaz On the Expression Of Klf4 And Nf-κb P-p65 Amentioning
confidence: 99%